Imaging of intracellular sodium with shift reagent aided (23)Na CSI in isolated rat hearts. - Weidensteiner, C; Horn, M; Fekete, E; Neubauer, S; von Kienlin, M (2002)
23Na chemical shift imaging (CSI) in conjunction with shift reagents was used to obtain images of intracellular (Na(i)) and extracellular sodium (Na(e)) in isolated rat hearts. It was demonstrated that the increase of Na(i) concentration in ischemic myocardium can be detected with this technique. 3D acquisition-weighted (23)Na CSI datasets with a nominal spatial resolution of 1.7 x 1.7 x 2.9 mm were acquired in 30 min in normoxic hearts and in globally or locally ischemic hearts. The shift reagent Tm(DOTP)(5-) was used to discriminate Na(i) and Na(e) signals. Na(i) maps could be generated in ischemic hearts, but not in normoxic hearts as the signal-to-noise ratio is too low. The Na(i) signal increased by more than 100% and the Na(e) signal decreased by more than 50% in myocardium of globally ischemic hearts (n = 3) compared to normoxic hearts (n = 3). In hearts with an acute occlusion of the left anterior descending coronary artery (n = 3), there was a local Na(i) signal increase in the anterior wall in the range of 60-110% compared to remote, normoxic tissue.